Executing the School Literacy Movement Program within Islamic-Based Excellence Schools - Sari, Anggun Meilinda; Rezania, Vanda (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative study investigates the habituation phase of literacy movement programs in Indonesian elementary schools, particularly focusing on Islamic-based approaches. Through literature review of 10 relevant references from 2017 to 2020, the efficacy of pre-reading reflections in improving morning literacy skills is analyzed. The findings underscore the potential of this approach for broader implementation, emphasizing its significance in diverse educational settings, especially those with Islamic orientations. Highlights : Islamic-based approach: Analyzing the effectiveness of Islamic-oriented strategies in enhancing literacy skills among elementary school students. Pre-reading reflections: Investigating the impact of 10 pre-reading reflections on morning literacy skills during the habituation phase. Diverse educational settings: Highlighting the potential for broader implementation of tailored literacy programs, especially in schools with Islamic curriculums. Keywords: literacy movement, elementary schools, Islamic curriculum, habituation phase, qualitative research